2016
DOI: 10.1051/swsc/2016007
|View full text |Cite
|
Sign up to set email alerts
|

Making of a solar spectral irradiance dataset I: observations, uncertainties, and methods

Abstract: Context. Changes in the spectral solar irradiance (SSI) are a key driver of the variability of the Earth's environment, strongly affecting the upper atmosphere, but also impacting climate. However, its measurements have been sparse and of different quality. The ''First European Comprehensive Solar Irradiance Data Exploitation project'' (SOLID) aims at merging the complete set of European irradiance data, complemented by archive data that include data from non-European missions. Aims. As part of SOLID, we prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 56 publications
(21 reference statements)
1
25
0
Order By: Relevance
“…Furthermore, the short-term and long-term uncertainties of the SSI time series are determined. These steps are detailed in Schöll et al (2016).…”
Section: Solid Compositementioning
confidence: 99%
“…Furthermore, the short-term and long-term uncertainties of the SSI time series are determined. These steps are detailed in Schöll et al (2016).…”
Section: Solid Compositementioning
confidence: 99%
“…Ly α line is important for the proper simulation of terrestrial atmospheric temperature and chemistry. Schöll et al (2016) analysed the results of the radiative transfer code COSI and reported that both the absolute value and variability of the reconstructed Ly α flux are strongly underestimated. The disagreement with the absolute value has been resolved by using NESSY, the new version of the radiative transfer code, which is able to properly simulate solar irradiance below 130 nm (see Tagirov et al (2017) for details).…”
Section: The Ly α Linementioning
confidence: 99%
“…As recent studies have demonstrated (e.g. Schöll et al, 2016), the solar spectra measured from satellite platforms can differ significantly between each other, due in part to instrument degradation issues arising from the harsh space environment and the difficulties in accounting for possible instrument changes between the preflight calibration and its operation in space. In a strict metrological sense, such measurements cannot be considered traceable to SI (International System of Units) since metrological traceability inherently requires the repeated demonstration of the uninterrupted traceability to primary standards, which is currently not available to instruments located in space (https://www.nist.gov/traceability/ supplementary-materials-nist-policy-review#internal_map).…”
Section: Introductionmentioning
confidence: 99%